A longitudinal study of sprinting and agility in children, a case of junior athletes in a talent identification and development program - Tanisho, K.; Ikarugi, H.; Yano, T.; Kaya, M.; Nagano, T.; Hirakawa, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
A study was conducted to investigate the relationship between sprinting ability and agility using a longitudinal design. The subjects were 70 junior athletes (39 boys and 31 girls) aged 9 to 12 years participating in a Talent Identification and Development program. Physical constitution (height and body weight), 20-m sprint test time, rebound jump index, and ability to change direction (agility test and T-run test) were measured periodically for three years. The main results were as follows: 1. Physical constitution, sprinting ability, rebound jump index, and ability to change direction increased significantly along with development in both boys and girls. 2. Performances in the 20-m sprint, agility test, and T-run test in boys were significantly better than in girls, but no significant sex difference was observed in the rebound jump index. 3. Single correlation analysis demonstrated significant correlations between all of the tests. 4. Partial correlation analysis (using age in months as the control variable) revealed significant relationships between the agility test and T-run test in boys and girls, but correlations between 20-m sprint ability and the agility test or T-run test were not significant. 5. There was little difference in the rebound jump index between boys and girls, and it was suggested that ability to change running direction was less affected by simple sprinting or strength-shortening cycle abilities during the developmental period.